Assessing Population Diversity of Brettanomyces Yeast Species and Identification of Strains for Brewing Applications - Colomer, Marc Serra; Chailyan, Anna; Fennessy, Ross T.; Olsson, Kim Friis; Johnsen, Lea; Solodovnikova, Natalia; Forster, Jochen (Frontiers in Microbiology, 2020)
Brettanomyces yeasts have gained popularity in many sectors of the biotechnological industry, specifically in the field of beer production, but also in wine and ethanol production. Their unique properties enable Brettanomyces to outcompete conventional brewer’s yeast in industrially relevant traits such as production of ethanol and pleasant flavors. Recent advances in next-generation sequencing (NGS) and high-throughput screening techniques have facilitated large population studies allowing the selection of appropriate yeast strains with improved traits. In order to get a better understanding of Brettanomyces species and its potential for beer production, we sequenced the whole genome of 84 strains, which we make available to the scientific community, and carried out several in-vitro assays for brewing-relevant properties. The collection includes isolates from different substrates and geographical origin. Additionally, we have included two of the oldest Carlsberg Research Laboratory isolates. In this study, we reveal the phylogenetic pattern of Brettanomyces species by comparing the predicted proteomes of each strain. Furthermore, we show that the Brettanomyces collection is well described using similarity in genomic organization, and that there is a direct correlation between genomic background and phenotypic characteristics. Particularly, genomic patterns affecting flavor production, maltose assimilation, beta-glucosidase activity and phenolic off-flavor production are reported. This knowledge yields new insights into Brettanomyces population survival strategies, artificial selection pressure and loss of carbon assimilation traits. On a species-specific level, we have identified for the first time a Phenolic Off-Flavor (POF) negative Brettanomyces anomalus strain, without the main spoilage character of Brettanomyces species. This strain (CRL-90) has lost DaPAD1, making it incapable of converting ferulic acid to 4-ethylguaiacol and 4-ethylphenol. This loss of function makes CRL-90 a good candidate for the production of characteristic Brettanomyces flavors in beverages, without the contaminant increase in POF. Overall, this study displays the potential of exploring Brettanomyces yeast species biodiversity to find strains with relevant properties applicable to the brewing industry.